The Association of Aging and Aerobic Fitness With Memory - Bullock, Alexis M.; Mizzi, Allison L.; Kovacevic, Ana; Heisz, Jennifer J. (Frontiers in Aging Neuroscience, 2018)
The present study examined the differential effects of aging and fitness on memory. Ninety-five young adults and eighty-one older adults performed the Mnemonic Similarity Task to assess high-interference memory and general recognition memory. Age-related differences in high-interference memory were observed across the lifespan, with performance progressively worsening from young to old. In contrast, age-related differences in general recognition memory were not observed until after 60 years of age. Furthermore, older adults with higher aerobic fitness had better high-interference memory, suggesting that exercise may be an important lifestyle factor influencing this aspect of memory. Overall, these findings suggest different trajectories of decline for high-interference and general recognition memory, with a selective role for physical activity in promoting high-interference memory.